DEFINITION AND FORMAL REPRESENTATION OF THE PROJECT MANAGEMENT PROCESSES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Project management information systems are used to support project management processes. The typical project management processes are defined by the project management methodologies, such as PMBOK. It is necessary to formalize representation of these processes to use them in modelling, analysis and implementation of the project management information systems. The purpose of the article is defined key processes of project management and to identify appropriate techniques and tools for their formal representation. In the article groups of the project management processes are listed and representation techniques such as UML, XPDL and YAWL are evaluated. The comparison of process representation techniques is shows that the most appropriate is XPDL. Guidelines for project management process definition using XPDL are formulated. These formalized processes further will be used in configuration of the project management information systems.